AGGREGATE ACCOUNTING EARNINGS, CAPITAL MARKETS AND GDP GROWTH: A CONCEPTUAL STUDY - Ibrahim, Mohammad Azhar; Jeh, Philip (CENTRAL ASIA AND THE CAUCASUS, 2021)
Recent studies show that macroeconomic research has evolved the accounting research independency focusing on economic indices, without incorporating accounting aggregates. This paper seeks to investigate the informativeness of aggregate accounting earnings obtainable from the capital markets on Gross Domestic Product (GDP) growth. It potentially identifies the support base and framework for inclusion of accounting earnings aggregate into GDP compilations. The paper has implications for current practice in GDP computations as well as widening accounting research to macroeconomic level, as against individual firm-level.